APLIKASI RASIONAL EMOTIF TERAPI DALAM MEMPERBAIKI PERILAKU MEMBOLOS SISWA - Isop Syafei (Psympathic : Jurnal Ilmiah Psikologi, 2010)
Today, education face many kind of problems that indicate student maladjustment behavior. All sorts of students maladjustment behavior stretch from the lower level to the higher level. For example; cut class, engage in the gang fight, hold-up, free sex and consume the narcotics. Counseling is the process of connection between counselor and counselee that help the counselee solve the problem to find the behavior that conform the rule of the society. Albert Ellis sparked the theory of rational emotive therapy that give the assumption that human had brought the potential to think rationally, honest, and think irrationally and bad. Human has two tendencies, they are positive and negative tendencies.The rational emotive therapy using ABCD analysis can help the counselor to understand the client’s problem holistically.